HERLYN-WERNER-WUNDERLICH SYNDROME-ROLE OF IMAGING IN TIMELY AND CORRECT DIAGNOSIS - Hidayat Ullah (Pakistan Armed Forces Medical Journal, 2021)
We present this case of uterus didelphys with right sided haematometrocolpos due to obstructed hemivagina and ipsilateral renal agenesis-Herlyn Werner Wunderlich syndrome. The condition was missed on ultrasound and diagnosed on plain CT scan abdomen and pelvis. This syndrome should be kept in mind while dealing with a young female complaining of lower abdominal pain and a pelvic mass having unilateral renal agenesis and an ipsilateral pelvic cystic lesion on ultrasound or other imaging modality. Timely diagnosis is important to avoid complications like pyocolpos and retrograde spilling of blood with consequent endometriosis. Imaging plays a major role in a correct and timely diagnosis.